A Novel Design of Voltage Controlled Oscillator By using the Method of Negative Resistance - Ayoub Malki; Larbi El Abdellaoui; Jamal Zbitou; A. Errkik; A. Tajmouati; Mohamed Latrach (International Journal of Electrical and Computer Engineering (IJECE), 2018)
The objective of this paper is to develop a new design of a voltage controlled microwave oscillator by using the method of negative resistance in order to fabricate VCO with very good performance in terms of tuning rang, phase noise, output power and stability. The use of hybrid microwave integrated circuit technology’s (HMIC) offers a lot of advantage for our structure concerning size, cost, productivity, and Q factor. This VCO is designed at [480MHz; 1.4GHz] frequency for applications in the phase locked loop (PLL) for signal tracking, FM demodulation, frequency modulation, mobile communication, etc. The different steps of studied voltage controlled oscillator’s design are thoroughly described. Initially designed at a fixed frequency meanwhile the use of a varactor allow us to tune the frequency of the second design. It has been optimized especially regarding tuning bandwidth, power, phase noise, consumption and size of the whole circuit. The achieved results and proposed amendment are the product of theoretical study and predictive simulations with advanced design system microwave design software. A micro-strip VCO with low phase noise based on high gain ultra low noise RF transistor BFP 740 has been designed, fabricated, and characterized. The VCO delivers a sinusoidal signal at the frequency 480 MHz with tuning bandwidth 920 MHz, spectrum power of 12.62 dBm into 50 Ω load and phase noise of -108 dBc/Hz at 100 Hz offset. Measurement results and simulation are in good agreement. Circuit is designed on FR4 substrate which includes integrated resonators and passive components.